From the editors - Editors (Zagłada Żydów)
This volume contains a selection of articles from Holocaust. Studies and Materials published by the Centre for Holocaust Research during 2014–2016. This is already the fourth English volume intended to familiarise the foreign reader with the newest Polish research on the Holocaust and also introducing unknown documents from Polish archives into scholarly circulation. The previous editions were published in 2008, 2010, and 2013.